Issues of commercialization activities of biotechnology-related researches in Malaysian research universities - Yaacob, Noorulsadiqin; Mohamed Ismail, Risyawati; Md Rasli, Amran (Universiti Utara Malaysia, 2011)
This study aims to explore issues of commercialization activities of research results among academic researchers who work in biotechnology-related researches in Malaysian Research Universities.Accordingly, the conceptual framework based on the ‘Innovation Implementation’ model has been assessed for its applicability in describing the phenomenon under study. Through interviews, elements as specified in the ‘Innovation Implementation’ model were found in this case study. Significant patterns and themes were also identified that suggest local industries, funding for research, development and commercialization as well as leadership, political interference, researcher’s attitude, transition management and legal perspectives are considered as the contextual factors that affect the commercialization activities of research results.Finally, the revised framework of commercialization-activities implementation based on the findings from qualitative analysis was recommended.